Caregivers Experience in Performing Interpersonal Communication and Directive Speech Acts With Elderly in Japan and Bali Nursing Home - Ni Komang Purwaningsih; Agus Darma Yoga Pratama (RETORIKA: Jurnal Ilmu Bahasa, 2020)
An increasing number of elderly in Japan and Indonesia, especially Bali, has led to increased health needs to care for them in nursing homes. Health workers, such as caregivers, are the closest people to communicate directly with the elderly. Communication can be called interpersonal communication which is a process of direct information or transfer of understanding of two or more people. Good interpersonal communication will build closeness and intimacy in the process of delivering messages. Therefore this study tried to analyze the experience of caregivers in implementing interpersonal communication and also determine the form of directive speech acts used by caregivers in caring for the elderly in nursing homes. The method used in this research was a qualitative descriptive method by phenomenological approach. The results showed that interpersonal communication applied by caregivers in caring for the elderly provided verbal and non verbal interpersonal communication. In addition, in the communication process of caregive-elderly is also formed directive speech act including prohibitions, requests and questions. In conclusion, caregivers need to have the ability to communicate effectively with elderly.